'Seeing a conspiracy around every corner': Paranoia as procedural in Tony Marchant's The Whistleblowers (2007). (September 2019) - Oldham, Joseph
The Whistleblowers is an unusual example of a British television conspiracy drama. Developed by Tony Marchant for ITV as a competitor to the BBC's Spooks, it centred on ordinary people struggling with the ethics of reporting malpractice in state or corporate institutions. This was invested with verisimilitude through advice from the whistleblowing charity Public Concern at Work, though kept in tension with generic expectations of the conspiracy thriller. Unlike most British conspiracy dramas, The Whistleblowers was not a serial but a procedural with stand-alone episodic conspiracies, creating a vision of conspiracy not as escalating crisis but as 'standard operating procedure'.